Citalopram administration does not promote function or histological recovery after spinal cord injury - Lima, Rui (2020)
Citalopram is a selective serotonin reuptake inhibitor, and although widely used as an antidepressant, this drug has also demonstrated interesting repairing properties leading to motor recovery and pathology amelioration in animal models of stroke and degeneration. Here, we tested the efficacy of both 7-day and 8-week citalopram treatment in a contusive spinal cord injury (SCI) rat model. A combination of behavioral tests, histological and serum cytokine analysis was used to assess overall recovery. Despite promoting a mild reduction of inflammatory cells as well as an early, but transient increase of specific serum cytokines, citalopram administration showed no overall beneficial effects on motor performance or lesion extension. Our results do not support citalopram treatment as a therapeutic strategy for SCI.